Age differences in prospective memory for everyday life intentions: A diary approach. Issue 4 (20th April 2016) - Schnitzspahn, Katharina M.; Scholz, Urte; Ballhausen, Nicola; Hering, Alexandra; Ihle, Andreas; Lagner, Prune; Kliegel, Matthias
Abstract : The age benefit found in many naturalistic prospective memory (PM) tasks has been taken as evidence that PM performance in real life may be spared from aging. However, this conclusion lacks empirical confirmation. Hence, the aim of the present study was to examine possible age differences in the content of everyday PM intentions and their performance. Everyday PM was assessed in young and older adults using a diary approach. Results confirmed a general age benefit for real-life PM tasks. Importantly, this finding was qualified by revealing that the benefit only held true for specific types of intentions such as health and social intentions. Further, moderation analyses showed that the relationships between cognitive functioning and everyday PM were different for young and older adults. While better inhibition, short-term and long-term memory were related with successful PM performance in the young, this was not the case in the older adults. The present findings suggest that the age benefit found in naturalistic experimenter-given tasks extends to real-life PM performance, but may differ depending on the type of intention. Furthermore, cognitive functioning predicts performance in the young, but not in the older adults.